Thermomechanical pulping (TMP), chemithermomechanical pulping (CTMP) and biothermomechanical pulping (BTMP) of bugweed (Solanum mauritianum) and Pinus Patula - Vena, P. F. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Forest and Wood Science))—University of Stellenbosch, 2005.